Förderung interkultureller Kompetenz auf geographischen Exkursionen – eine empirische Studie - Schrüfer, Gabriele (Zeitschrift für Geographiedidaktik (ZGD), 2011)
Intercultural competence as the objective of intercultural learning is part of the key qualifications of our society. In order to develop intercultural competence learning by experience through contact with other cultures is often assumed as essential. However, the literature shows diverse results whether cultural interactions on travels really support intercultural competence. Particularly in studies about students exchange it was noticed that especially direct contact with different cultures might consolidate attitudes and strengthen prejudices. There are no empirical studies which focus on the promotion of intercultural competence on geographic field trips so far. The main question of this empirical study is: which conditions does a field trip have to impose in order to develop intercultural competence? A nineteen-day field trip with nineteen students to Tanzania served as a research approach. The research design consists of a quantitative and a qualitative study. The qualitative study comprises diaries and interviews. The quantitative study refers to a questionnaire. First, with the use of the questionnaire, it was found that intercultural competence develops in different ways among students during a field trip. With the help of the diaries, which were both quantitatively and qualitatively evaluated, three different types could be identified. Thereby conclusions could be drawn to encouraging and retarding factors of developing intercultural competence.
Keywords: Intercultural Education, Intercultural Competence, Field Trips, Africa, Model of Intercultural Learning